2023
DOI: 10.3390/pr11113141
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Microwave and Ultrasound-Assisted Extraction as a Green Tool for Polyphenolic Isolation from Monofloral Honeys

Sandra Pedisić,
Patricija Čulina,
Tomislav Pavlešić
et al.

Abstract: Monofloral honey is obtained from the nectar of single-source plants and has a higher market value due to its polyphenol content associated with its biological properties, especially its antioxidant capacity. In this work, advanced extraction techniques using microwave- (MAE) and ultrasound-assisted (UAE) extraction of phenolic compounds in monofloral honey were optimized and compared. Optimal parameters for MAE were an irradiation time of 15 min, a temperature of 60 °C, and a microwave power of 300 W, and for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…At higher ultrasound power, cavitation phenomena can initiate new reaction mechanisms, i.e., bubble destruction, degassing, and free radical formation, and cause changes in temperature, pressure, and physical interaction between solid and liquid interfaces that favor the degradation of BAMs [80]. Borrás-Enríquez et al [81] and Pedisić et al [82] found that the optimal ultrasonic power for obtaining extracts with high TPC and AA in mango residues and monofloral honeys is 60%, which is consistent with our study. In addition, temperature can affect the integrity of BAMs, as most of them are thermolabile.…”
Section: Optimization Of the Uae Of Polyphenols From Sb Cakementioning
confidence: 99%
“…At higher ultrasound power, cavitation phenomena can initiate new reaction mechanisms, i.e., bubble destruction, degassing, and free radical formation, and cause changes in temperature, pressure, and physical interaction between solid and liquid interfaces that favor the degradation of BAMs [80]. Borrás-Enríquez et al [81] and Pedisić et al [82] found that the optimal ultrasonic power for obtaining extracts with high TPC and AA in mango residues and monofloral honeys is 60%, which is consistent with our study. In addition, temperature can affect the integrity of BAMs, as most of them are thermolabile.…”
Section: Optimization Of the Uae Of Polyphenols From Sb Cakementioning
confidence: 99%